2013
DOI: 10.1590/abd1806-4841.20132046
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by S. Aureusincreases the EASI and the number of appointments by patients with atopic dermatitis: cohort with 93 patients

Abstract: BACKGROUNDAtopic dermatitis leads to epidermal barrier dysfunction and bacteria colonization. The relationship of the last factor with the severity of the disease and the frequency of exacerbation is not fully known. OBJECTIVESVerify the severity of the atopic dermatitis and the number of appointments generated by dermatosis, comparing patients colonized with patients not colonized by S. aureus. Verify the frequency of colonization by methicillin resistant Staphylococcus aureus acquired in the community. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…This could interpret the high rate of colonization in our study as more than half of our cases were severe AD. Patient with AD has increased risk of increasing antibiotic resistance due to the frequent use of topical and systemic antibiotics (Lipnharski et al 2013). In this study, a high rate of antibiotic resistance was reported.…”
Section: Discussionmentioning
confidence: 58%
“…This could interpret the high rate of colonization in our study as more than half of our cases were severe AD. Patient with AD has increased risk of increasing antibiotic resistance due to the frequent use of topical and systemic antibiotics (Lipnharski et al 2013). In this study, a high rate of antibiotic resistance was reported.…”
Section: Discussionmentioning
confidence: 58%
“…There are a number of potential risk factors for infections to occur in AD patients, including skin-barrier dysfunction secondary to decreased expression of epidermal lipids and mechanical disruption from scratching 21 , decreased expression of anti-microbial peptides 22 , aberrant Toll-like receptor signaling and innate immunity 23 , 24 , increased colonization with Staphylococcus aureus in lesional and non-lesional skin 25 , 26 , and use of topical and/or systemic immunosuppressing medications (e.g. corticosteroids, calcineurin inhibitors, etc.).…”
Section: Infectionsmentioning
confidence: 99%
“…Skin barrier defects are a hallmark in AD and facilitate penetration and entry of microbes, giving patients with AD a predisposition to microbial skin infections . Up to 90% of patients with AD are colonized with Staphylococcus aureus , and despite a strong link between disease severity and S. aureus colonization, the precise role of S. aureus in the pathogenesis of AD is still unclear …”
mentioning
confidence: 99%